Analisis T2Sanstore Membangun Brand Engagement TikTok - Marcella, Cherise; Aulia, Sisca (Prologia, 2025)
As time goes by, people are increasingly easy to share information and interact through social media. Where users not only share information but also can express themselves, One of these social media is TikTok, not only used to express themselves, TikTok is also used by business people to create a brand image of a product. One of them is @T2Sanstore which also uses TikTok as a platform to provide information about automotive and entertainment products. The purpose of this study is to analyze the engagement of @T2Sanstore TikTok content. Researchers used a qualitative method with a case study, data collection in the study used the Observation, Interview and Documentation methods. The results of this study stated that the level of engagement varies and can be caused by differences in the types of products being promoted. For example, automotive products tend to attract the attention of certain age and gender segments, while other products such as children's bags can be more attractive to parents and children. This factor presents a challenge in achieving engagement stability so that it is different or varied. Customer Engagement is important because engaged users tend to be more loyal, promote the brand naturally, and have a higher level of satisfaction. Therefore, T2Sanstore focuses on customer engagement strategies as an integral part of their marketing strategy and customer interaction relationship management. Seiring berjalannya waktu, masyarakat semakin mudah berbagi informasi dan interaksi melalui media sosial. Dimana para pengguna tidak hanya berbagi informasi namun juga dapat mengekspresikan diri sendiri, Salah satu media sosial tersebut adalah Tiktok, tidak hanya digunakan untuk mengekspresikan diri, Tiktok juga dimanfaatkan oleh para pebisnis untuk menciptakan brand image suatu produk. Salah satunya adalah @T2Sanstore yang juga memanfaatkan Tiktok sebagai wadah tempat memberikan seputar informasi produk produk otomotif dan hiburan. Tujuan Penelitian ini adalah untuk menganalisis engagement dari konten Tiktok @T2Sanstore. Peneliti menggunakan metode kualitatif dengan studi kasus, pengumpulan data pada penelitian menggunakan metode Observasi, Wawancara dan Dokumentasi. Hasil penelitian ini menyatakan tingkat engagement bervariasi dan dapat disebabkan oleh perbedaan jenis produk yang dipromosikan. Sebagai contoh, produk otomotif cenderung menarik perhatian segmen usia dan gender tertentu, sementara produk lain seperti tas anak dapat lebih menarik bagi orang tua dan anak anak. Faktor ini memunculkan tantangan dalam mencapai stabilitas engagement sehingga berbeda atau bervariasi. Customer Engagement menjadi penting karena pengguna yang terlibat cenderung lebih setia, mempromosikan merek secara alami, dan memiliki Tingkat kepuasan yang lebih tinggi. Oleh karena itu, T2Sanstore berfokus pada strategi customer engagement sebagai bagian integral dari strategi pemasaran dan pengelolaan hubungan interaksi costumer mereka.